On Joint Cost Allocation: Independent Cost Proportional Scheme (ICPS) and Its Properties - Gangolly, Jagdish S. (Journal of Accounting Research, 1981)
Cost allocation, Independent Cost Proportional Scheme, Joint costs, Moriarity scheme